Technical efficiency comparison of container ports in Asian and Middle East region using DEA - Faluk Shair Mustafa; Rafi Ullah Khan; Tariq Mustafa (Asian Journal of Shipping and Logistics (AJSL), 2021)
With the instigation of China Pakistan Economic Corridor (CPEC), the strategic significance of South Asian and Middle Eastern ports have been vitalized. The aim of this study is to compare the technical efficiency of less explored South Asian & Middle Eastern ports with the East Asian ports and determine ways for their efficiency enhancement and management optimization. The cross sectional data for the year 2018 was collected for 15 container ports each of South & Middle Eastern and East Asian region and arranged into input and output variables. The data was analyzed through the DEA-CCR and DEA-BCC model. Results indicate that only one port each from UAE and India among the Middle & South Asian ports were found efficient on CCR model with the number of efficient ports on BCC model increased by 47%. While, in East Asian region two ports of China and one of South Korea were found efficient on CCR model, with 33% increase on BCC model. Lianyungang port was the most prominent among the efficient ports being highly benchmarked. The average efficiency for East Asian region (CCR: 0.524, BCC: 0.901) remained similar to that of South Asian and Middle East Region (CCR: 0.517, BCC: 0.906).
Keywords: 650; Data Envelopment Analysis; Comparative efficiency; Belt and Road Initiative; Middle East and South Asian region; East Asian region; Port efficiency